Benzannulation via Ruthenium-Catalyzed Diol–Diene [4+2] Cycloaddition: One- and Two-Directional Syntheses of Fluoranthenes and Acenes - Geary, Laina M; Chen, Te-Yu; Montgomery, T. Patrick; Krische, Michael J (Journal of the American Chemical Society, 2014)
A new benzannulation protocol is described and applied to the synthesis of polycyclic aromatic hydrocarbons. Ruthenium(0)-catalyzed diol–diene [4+2] cycloaddition delivers cyclohex-1-ene-4,5-diols, which are subject to aromatization upon dehydration or Nicholas diol deoxydehydration. Employing diol and tetraol reactants, benzannulation can be conducted efficiently in one- and two-directional modes, respectively, as illustrated in the construction of substituted fluoranthenes and acenes.